Analysis of The Main Components Forming the Business Development Model of Technological Ideas in Iranian Research Institutes - Abdi, Nariman; Torabi, Taghi; Radfar, Reza (International Journal of Engineering and Technology, 2018)
The purpose of this article is to present the main components forming business development model of technological ideas in Iranian research organizations. This research is fundamental objectively (empirical fundamental research) and it is non-experimental in terms of data collection method (acquisitive research) and according to the research approach is qualitative. This research was implemented with a multiple case study strategy, which ultimately the research objective will be realized by identifying the steps, the activities of main beneficiaries and the contributing factors in the business development of technological ideas derived from case studies with each other and with the research literature. The study population included research institutes and government research institutes covered by the Ministry of Science, Research and Technology, Ministry of Health, Medical Education, or other executive agencies. Based on the systematic elimination sampling method, the Petroleum Research Institute, Agricultural Biotechnology Research Institute, Botanical Research Institute, Research Center of Medical Science and Technology, Pasteur Institute of Iran and the University Jihad were selected. Direct observation, interviewing and studying documents were used to collect data of this research. Tools of content analysis, within-case and cross-case analyzes were selected for analyzing information from several case studies for analyzing information and comparing research results with subject literature. The results showed that the main components forming business development model of technological ideas in Iran's state research institutes consisted of five main stages, 15 executive steps, 8 key activities, and beneficiaries, and intra and extra organization factors.Â Â